Respuesta :

Answer:

height = (3x + 3)

Step-by-step explanation:

area of rectangular prism = length *breadth

2x^2 + 3x = length*breadth

volume of a rectangular prism = length * breadth *height

6x^3 + 13x^2 + 6x = (2x^2 + 3x) *height

x(6x^2 + 13x + 6) = x(2x + 3) *height

a nd x gets cancel . So,

(6x^2 + 13x + 6) = (2x + 3) *height

6x^2 + (9 + 4)x + 6 = (2x + 3) *height

6x^2 + 9x + 4x + 6 = (2x + 3) *height

3x(2x +3) +2(2x +3) = (2x + 3) *height

(3x + 2)(2x + 3) = (2x + 3)*height

(3x + 2)(2x + 3) / (2x + 3) = height

(2x + 3 ) of numerator and (2x + 3) of denominator gets cancel

(3x + 3) / 1 = height

(3x + 3) = height